Oral phenotype and scoring of vascular Ehlers–Danlos syndrome: a case–control study - Lisa Golmard; Ariane Berdal; François Côme Ferré; Michael Frank; Bruno Gogly; Adrien Naveau; Hafida Chérifi; Joseph Emmerich; Frédérick Gaultier; Xavier Jeunemaitre; Benjamin P J Fournier (BMJ Open)
Objective Vascular Ehlers–Danlos syndrome (vEDS) is a rare genetic condition related to mutations in the COL3A1 gene, responsible of vascular, digestive and uterine accidents. Difficulty of clinical diagnosis has led to the design of diagnostic criteria, summarised in the Villefranche classification. The goal was to assess oral features of vEDS. Gingival recession is the only oral sign recognised as a minor diagnostic criterion. The authors aimed to check this assumption since bibliographical search related to gingival recession in vEDS proved scarce.Design Prospective case–control study.Setting Dental surgery department in a French tertiary hospital.Participants 17 consecutive patients with genetically proven vEDS, aged 19–55 years, were compared with 46 age- and sex-matched controls.Observations Complete oral examination (clinical and radiological) with standardised assessment of periodontal structure, temporomandibular joint function and dental characteristics were performed. COL3A1 mutations were identified by direct sequencing of genomic or complementary DNA.Results Prevalence of gingival recession was low among patients with vEDS, as for periodontitis. Conversely, patients showed marked gingival fragility, temporomandibular disorders, dentin formation defects, molar root fusion and increased root length. After logistic regression, three variables remained significantly associated to vEDS. These variables were integrated in a diagnostic oral score with 87.5% and 97% sensitivity and specificity, respectively.Conclusions Gingival recession is an inappropriate diagnostic criterion for vEDS. Several new specific oral signs of the disease were identified, whose combination may be of greater value in diagnosing vEDS.